A proposal for a quality system for herbal products - Pan, S.; Neeraj, A.; Srivastava, K.; Kishore, P.; Danquah, Michael; Sarethy, I. (John Wiley & Sons Inc, 2013)
Today, there is an increasing worldwide demand for botanicals. Developing countries heavily rely on plant-derived medicines for their primary healthcare. One reason amongst many is the relatively inexpensive process economics and the lack of stringent product governance associated with the exploitation of traditional plant medicines compared with modern medicine. Developed countries impose stringent good manufacturing practices and quality control measures on drug products derived from any manufacturing process, regardless of the primary raw material. However, several factors hamper the full-scale application of traditional plant medicines: lack of implementation of effective quality assurance in the manufacturing process; lack of traceability in the supply chain and associated value additions; and inefficient identification of molecular species that affect the therapeutic efficacy of the final product. There lacks an assessable, causative, and prognostic relationship between the raw materials, the manufacturing process and the final product quality. This article suggests some solutions that may be adopted by the phytodrug industry to widen its global reach and retain its credibility. Primarily among them is the implementation of hazards analysis and critical control point in the manufacturing process and employment of process analytical technology for ensuring minimal deviation from the manufacturing process of phytotherapeutics.